Development of Hydrosphere Geography Learning Media to Improve Higher Order Thinking Skills (HOTS) - HSB, Titin Suprayatini; Mukminan, Mukminan (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to: (1) develop geography learning media on hydrosphere material to improve higher-order thinking skills (HOTS) and (2) Know the effectiveness of Web-based application media development products to improve the ability of Higher Order Thinking skills (HOTS). This research is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of the small-scale trial were 36 students, the large scale was 72 students, and the effectiveness test subjects were 108 students. The effectiveness test used a one-group pre-test post-test design experiment. Data analysis used a paired sample t-test with a significance level of 0.05. The results demonstrated that: (1) based on Gregory's validation the material experts' validation was very high with a construct validity value of 0.81, and the media experts' validation was very high with a construct validity value of 1. Practicality validation conducted by teachers in small and large fields shows a construct validity value of 1. (2) The web-based application media improved higher-order thinking Skills (HOTS), with effectiveness demonstrated by the results of a paired sample t-test analysis showing a significance value of 12.83, which is greater than the critical value of 2.045. The Web-based application media positively impacted the ability of higher-order thinking Skills (HOTS) in geography learning.